Voices in Climate Change Adaptation: Roles of Females Despite Resource Inaccessibility During Floods in Gampaha, Sri Lanka - Darshika, Nimali; Trafford, Julie; Kumari, Sujeewa; Wickramasinghe, Deepthi (Emerald, 2026)
Purpose Focusing on Gampaha, Sri Lanka’s most densely populated district, this research aims to explore the lived experiences, vulnerabilities and adaptive strategies of 25 women and girls aged 10 to 76 years who faced increasing frequency and severity of recurrent flooding. The district’s low-lying coastal terrain, rapid urbanization and unsustainable development practices exacerbate flood risks, as a gendered issue with disproportionate impacts on women and girls. Design/methodology/approach This study was designed by women, for women, with all-women expert researchers personally conducting interviews with women and girl respondents. When participants struggled to verbally express their experiences, particularly the gendered impacts of climate change-induced flooding, they were invited to draw their perceptions, which were then discussed in depth. Findings While only seven participants were familiar with the term “climate change” all could identify environmental changes such as irregular rainfall and increased flood frequency. Reported impacts included the destruction of homes and infrastructure, reduced income opportunities, education disruptions and health challenges, particularly related to sanitation and hygiene. Twenty-one of the respondents had lived in the area for over a decade and described intensified responsibilities during floods, including food preparation and community support, despite minimal involvement in formal disaster planning. Most respondents said women’s caregiving roles made evacuations during floods more difficult. Fifteen of the 25 participants expressed dissatisfaction with current flood management approaches, calling for improved healthcare, tailored support services and greater inclusion of women in preparedness and response planning. The findings underscore the urgency of integrating gender-responsive and intergenerational measures into climate adaptation strategies in flood-prone regions. Research limitations/implications This research collects data about women and girls within one of the most population dense and rapidly growing, yet poor, urban districts in Sri Lanka. Such research has not been undertaken to date. The data collected is limited to women and girls in this district. Practical implications The findings underscore the urgency of integrating gender-responsive measures into climate adaptation strategies in flood-prone regions. The findings also demonstrate the key roles that women and girls can play in flood mitigation and flood management. The roles that girls are expected to take on can mean that they are absent from formal education. Social implications This research is part of a broader project to train the trainers for mitigating and managing increased frequency and intensity of flooding due to climate change. Women leaders are trained to then train other women within the community. Originality/value To the best of the authors’ knowledge, this research, focusing specifically on the lived experiences of women and girls in Sri Lanka, has not been previously undertaken.
Keywords: 0502 Environmental Science and Management; 4101 Climate change impacts and adaptation; Climate change; Flooding; Gender; Girls; Sri Lanka; Women